Ästhetik und Poetik der Ruinen: Rekonstruktion - Imagination - Gedächtnis - Lombardi, Giulia; Oberto, Simona; Strohmaier, Paul (De Gruyter, 2022)
In ruins, the absence of the past achieves a maximum level of presence. At different points in time, fundamental reflections on the fragility of both human cultures and individual existence have taken shape around them, gaining significance in the fields of aesthetics, poetics, and the philosophy of history from the early modern period onward. This volume traces how ruins have transformed in Romance cultures up into the present day
Keywords: Aufsatzsammlung; Geschichte; Ästhetik; Geschichtsschreibung; Malerei; Romanische Sprachen; Literatur; Ruine; Künste